(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article highlights the socio-philosophical significance of leisure culture in the process of improving the spirituality of youth. It analyzes the ways of achieving personal perfection through meaningful leisure, the formation of a healthy lifestyle, the development of aesthetic taste and spiritual values. The article interprets leisure culture as an important factor in increasing a person’s mental stability, positive motivation, and creative potential. At the same time, the educational impact of new forms of cultural leisure in the digital age - virtual tourism, online art, and sports training - is being studied. According to the research results, it is substantiated that the promotion of cultural leisure traditions among young people is an important factor in strengthening their spiritual immunity, increasing national self-awareness and social activity